Predictors of survival rates among breast cancer patients in Ethiopia: a systematic review and meta-analysis 2024 - Chalie Mulugeta; Tadele Emagneneh; Getinet Kumie; Assefa Sisay; Nigusie Abebaw; Mulat Ayele; Abebaw Alamrew (Archives of Public Health)
Abstract Introduction Breast cancer remains the most common cancer and a leading cause of cancer-related deaths among women worldwide. In Ethiopia, the survival rate of breast cancer patients is influenced by various socio-demographic, clinical, and health system factors. This systematic review and meta-analysis aimed to identify and synthesize the predictors of survival rates among breast cancer patients in Ethiopia. Methods We conducted a systematic review of observational cohort studies. The literature search was performed between August 1 and 30, 2024, using PubMed, Hinari, EMBASE, Google, Google Scholar, and Web of Science. The Newcastle Ottawa 2016 Critical Appraisal Checklist assessed methodological quality. Publication bias was evaluated using a funnel plot and Egger’s test, and heterogeneity was examined with the I-squared test. Data were extracted with Microsoft Excel and analyzed using Stata 11. Results A total of 15 articles with 6,375 study participants from six regions were included. We found that significant predictors of decreased survival rate among breast cancer patients were age (aHR 1.05, 95% CI 1.02–1.08), illiteracy (aHR 7.34, 95% CI 4.38–10.3), married (aHR 1.21, 95% CI 1.03–1.40), rural residence (aHR 1.71, 95% CI 1.06–2.36), two or more lymph node involvement (aHR 3.57, 95% CI 1.02–6.13), histological grade two or more (aHR 1.44, 95% CI 1.12–2.77), overweight (aHR 0.56, 95% CI 0.24–0.87), and having comorbidity (aHR 1.86, 95% CI 1.04–2.68). Conclusion This systematic review and meta-analysis identified several key predictors of reduced survival rates among breast cancer patients in Ethiopia, including older age, illiteracy, rural residence, involvement of two or more lymph nodes, higher histological grade, marital status, and the presence of comorbidities. Interestingly, being overweight was associated with improved survival. Health stakeholders and policymakers emphasizing public health education, managing comorbidities, and expanding access to early detection and treatment, especially in rural areas, are critical.